Prevalence investigation of depression and associated risk factors in the elderly with hypertension in Yuetan community of Beijing - WANG Chunyuan, BIAN Lili, LI Xiaoxiao (Jichu yixue yu linchuang, 2023)
Objective To investigate the prevalence and risk factors of depression in elderly with hypertension in a community of Beijing, so as to provide evidence for individualized treatment of healthy aging. Methods Six hundred and thirteen elderly patients aged over 60 with hypertension were selected from Yuetan community of Beijing by overall sampling method from June 2019 to October 2019. Patient Health Questionnaire (PHQ-9) scale was used to determine depression. General demographic information, chronic diseases and health status of the subjects were collected at the same time. Single factor and binary logistic regression models were used to analyze the associated factors and independent risk factors of depression in elderly hypertensive patients of different genders. Results The overall incidence rate of depression in elderly hypertensive patients in the community was 11.58%, among which male accounted for 9.81% while female 12.53%. Univariate analysis showed that the incidence of depression in male elderly with hypertension was associated with sulfuring form coronary heart disease and sleep disorders, while in female associated with suffering from economic pressure, hearing impairment, vision impairment, chronic gastritis, chronic hepatobiliary diseases and sleep disorders, with a statistically significant difference (P＜0.05). Multivariate binary logistic regression analysis showed that male elderly with hypertension suffering from sleep disorders had a higher risk of depression, with an OR value of 4.825 (95% CI: 1.777-13.105), while female elderly sulfuring from economic pressure, hearing impairment, visual impairment, chronic gastritis and sleep disorders had a higher risk of depression, with OR values of 14.362 (95% CI: 2.224-92.747), 11.174 (95% CI: 2.535-49.258), 3.994 (95% CI: 1.444-11.043), 3.780 (95% CI: 1.608-8.887), 4.968 (95% CI: 2.430-10.156), respectively. Conclusions The prevalence of depression is high among the elderly with hypertension in Yuetan community of Beijing. The majority of elderly with hypertension showed mild degree depression. The incidence rates of elderly between genders are similar. Sleep disorder is an independent risk factor and economic stress, visual impairment, hearing impairment,chronic gastritis and sleep disorder as indepandent risk factors are more significant in old females with hypertension.